2018
DOI: 10.1002/clen.201800124
|View full text |Cite
|
Sign up to set email alerts
|

Radish (Raphanus sativus L.) Cultivar‐Specific Response to O3: Patterns of Biochemical and Plant Growth Characteristics

Abstract: The sensitivity of four radish (Raphanus sativus L.) cultivars, Baladey “B,” Cherry Belle “CB,” Prinz Rotin “PR,” and Scarlet Globe “SG” to 80 nL L−1 ozone is assessed in fumigation chambers. O3 visible injury symptoms appears as brown spots to chlorotic areas, but the response is cultivar‐specific. O3 induces higher content of H2O2 and lipid peroxidation (it is estimated as malondialdehyde (MDA) content), leading to drastic visible injury symptoms in B compared to the other cultivars. Root and shoot dry weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Research has shown that the CAT of Heterosigma erythraea (H. erythraea) also showed stress activity during the early stage of NAs exposure. However, with a continuous increase in exposure time, the CAT activity was significantly reduced and inhibited; hence, it was tolerated [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the CAT of Heterosigma erythraea (H. erythraea) also showed stress activity during the early stage of NAs exposure. However, with a continuous increase in exposure time, the CAT activity was significantly reduced and inhibited; hence, it was tolerated [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Treatments without biochar (0% biochar) were regarded as the control. The pot experiment was conducted using radish plant (Raphanus sativus) as a bio indicator for environmental pollution (Davies, 1993;Hassan et al, 2018). Five seeds were sown in each pot and water was added to bring the soil moisture to 70% of water holding capacity.…”
Section: Planting Experimentsmentioning
confidence: 99%
“…Net photosynthetic rate (A) and total CO 2 stomatal conductance (g s ) of the second true foliage leaf of each plant/treatment were measured with an open infrared gas exchange system (LI-6400, LICOR, Lincoln, NE, USA (Ismail et al 2014;Basahi et al 2016;Hassan et al 2018). Measurements were taken between 10:00 and 14:00 h (Egyptian local time) and were performed ten times at 7-day intervals in order to cover all growth stages of plant.…”
Section: Gas Exchange Measurementsmentioning
confidence: 99%
“…The saturation pulse method was used for analysis of quenching components as described by Hassan (2004;2006a). The light and dark fluorescence parameters were used for calculations of the following: actual quantum yield of PSII [Φ PSII = (F m , − F s ) / F m ] and photochemical [qP = (F m , − F s ) / (F m , − F 0 , )] and non-photochemical [(NPQ) = (F m − F m ) / F m , ] quenching coefficients (Pellegrini et al 2011(Pellegrini et al 2015Bashai et al 2016;Hassan et al 2018;Santos et al 2018).…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%
See 1 more Smart Citation